The Interleukin-20 Cytokines in Intestinal Diseases - Niess, Jan Hendrik; Hruz, Petr; Kaymak, Tanay (Frontiers in Immunology, 2018)
Autoimmune/inflammatory intestinal diseases, such as Crohn`s disease and ulcerative colitis, infectious gastrointestinal diseases and gastrointestinal cancers, such as colorectal cancer are worldwide a significant health problem. Intercellular communication and direct contact with the environment as the microbiota colonizes the gastrointestinal surface facilitates these diseases. Cytokines mediate the intercellular communication to maintain the equilibrium between host and environment and to regulate immune responses. One cytokine family that exchange information between immune cells and epithelial cells is the IL-20 cytokine family which includes the cytokines IL-19, IL-20, IL-22, IL-24, and IL-26. These cytokines share common receptor subunits and signaling pathways. IL-22 is the most intensively studied cytokine within this family in contexts of gastrointestinal disease, but the importance of other family members is more and more appreciated. In this review, the potential function of IL-20 cytokines concerning gastrointestinal conditions is discussed.